Analysis and Culture of the Broiler Gut Microbiome: A Step Towards Building a Disease-Resistant Microbial Consortia - Karwasra, Sakshi (My University, 2024)
Antimicrobial resistance poses a significant challenge to human health and is also a pressing One Health concern. The routine use of antibiotics as growth promoters in agricultural animals has contributed to the emergence of antibiotic resistance, which can subsequently affect human populations. Discontinuing this practice has led to a surge in infections and therapeutic antibiotic use in these animals. This increased susceptibility to infections may be linked, at least partially, to the loss of colonization resistance resulting from alterations in the microbiome. This study focuses on poultry, as the consumption of chicken meat can introduce antibiotic-resistant microbes into the human population. The overarching hypothesis for this research project is that a rationally designed consortium of microbes sourced from healthy chickens will increase colonization resistance and decrease susceptibility to infections as an alternative to growth-promoting antibiotics. The first goal was to analyze the broiler chicken’s gut microbiome and to establish a comprehensive culture collection of microorganisms from healthy chickens. Culture-enriched and culture-independent 16S sequencing was applied to assess the cultivability of the samples and to analyze their microbial profiles. Isolates were identified using MALDI-TOF and 16S rRNA gene sequencing. Frozen samples (from antibiotic-free farms) had a greater microbial diversity than fresh samples (from a university research facility). However, a greater proportion of the microbiome was recovered by culture from the fresh compared to the frozen samples. A strain collection of 1121 isolates representing 121 species was constructed. In Aim 2, I carried out a functional screen to identify isolates from the culture collection that inhibited the growth of the predominant poultry pathogens, E. coli and C. perfringens. Several isolates were identified that inhibited one or the other pathogens and a small number of isolates killed both pathogens. These microbes form the basis of therapeutic consortia to increase colonization resistance in chickens.
Analysis of Broiler Gut Microbiome Through Culturing
Keywords: Gut microbiome, broilers, 16S sequencing, extensive culturing, isolate collection